Sole and sequential application of herbicides and botanicals for weed management in summer sesame - Hota, Swastika; Dash, Subhaprada; B. Joshi, Utpal (Plant Science Today, 2024)
Weed infestation poses a significant challenge in sesame cultivation, leading to yield losses and decreased economic returns for farmers. The present study comprehensively analyses various weed control approaches, including allelopathic interaction with integrating herbicides and hand-weeding practices. The experiment was conducted at the Agriculture Farm, SOA, Odisha, during the summer of 2023 with 10 weed management treatments in RBD with 3 replications. The objective was to study different weed management practices, including the sole and sequential application of herbicides and botanicals, to control diverse weeds and enhance summer sesame growth, yield and profitability. The dominance of Digitaria sanguinalis (L.) Scop., Echinochloa colona (L.) Link. and Poa annua L. among grassy weeds and Melochia corchorifolia L., Cleome viscosa L. and Cassia tora L. among the broadleaved weeds were evident in summer sesame. The execution of different treatments showed that integrated use of aqueous leaf extract of Parthenium hysterophorus at 5 % concentration, followed by quizalofop-p-ethyl at 50 g/ha, was found on par with hand-weeding and brought down the weed count and biomass, which in turn increased the growth of summer sesame. The maximum yield of (793 kg seed/ha and 3035 kg stalk/ha) was registered under twice hand weeding. It was comparable with the spraying of aqueous leaf extract of Parthenium hysterophorus at 5 % concentration followed by (fb) quizalofop-p-ethyl at 50 g/ha (772 kg seed/ ha and 2968 kg stalk/ha). Economic analysis of sesame revealed that the maximum return (Rs. 37454/- per ha) and return/rupee (2.28) were recorded with aqueous leaf extract of P. hysterophorus at 5 % concentration fb quizalofop-p-ethyl at 50 g/ha treatment.